Science Applications of Phased Array Radars - Kollias, Pavlos; Palmer, Robert; Bodine, David; Adachi, Toru; Bluestein, Howie; Cho, John Y. N.; Griffin, Casey; Houser, Jana; Kirstetter, Pierre. E.; Kumjian, Matthew R.; Kurdzo, James M.; Lee, Wen Chau; et al. (Bulletin of the American Meteorological Society, 2022)
Phased array radars (PARs) are a promising observing technology, at the cusp of being available to the broader meteorological community. PARs offer near-instantaneous sampling of the atmosphere with flexible beam forming, multifunctionality, and low operational and maintenance costs and without mechanical inertia limitations. These PAR features are transformative compared to those offered by our current reflector-based meteorological radars. The integration of PARs into meteorological research has the potential to revolutionize the way we observe the atmosphere. The rate of adoption of PARs in research will depend on many factors, including (i) the need to continue educating the scientific community on the full technical capabilities and trade-offs of PARs through an engaging dialogue with the science and engineering communities and (ii) the need to communicate the breadth of scientific bottlenecks that PARs can overcome in atmospheric measurements and the new research avenues that are now possible using PARs in concert with other measurement systems. The former is the subject of a companion article that focuses on PAR technology while the latter is the objective here.